Sharia fintech: Crowdfunding as MSMEs financing - Hilma Rohmatul Ummah; Adang Sonjaya; Jujun Jamaludin (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
Fintech equity crowdfunding is now available in Indonesia, providing an alternative option for MSMEs to raise capital. As the majority of Indonesia's population is Muslim, sharia-based fintech equity crowdfunding is a more suitable option for those seeking funding according to Islamic principles. This system has the potential to be a capital solution for MSMEs more simply and ethically. This research aims to explore the potential of Sharia crowdfunding as an effective means for MSMEs to expand their business operations, ultimately contributing to broader economic sector improvements in Indonesia. Additionally, it assesses the conformity of this practice with OJK regulations and Fatwa DSN-MUI, as well as its compliance with Sharia principles. The descriptive-analytical method is employed, analyzing various documents and texts from various sources. The results indicate that Sharia-based fintech, particularly in the form of crowdfunding, can be an effective means for MSMEs to obtain capital through online platforms. Crowdfunding also presents opportunities for investors who wish to contribute to the funding of MSMEs in a manner that aligns with Sharia principles.